JOHN DEWEY SOCIETY, RATIONAL ARGUMENTS IN PHILOSOPHY OF EDUCATION - N. V. Tokarev (Дискурс, 2017)
The scientific articles written by the John Dewey Society members are poorly presented in Russian tradition of studying the philosophy of education. This article allows to re-evaluate the contribution of the American academic community in the process of teaching comprehension by the example of a detailed analysis of scientific works of Bertram Bandman, Harry Broudy, Sterling McMurrin et al. The core question «What should be taught?» is considered in the context of the search for rational arguments in the discussion, which lasts in the philosophy of education for decades. The heritage of the John Dewey Society members introduced into the Russian scientific circulation allows us to take a fresh view at the role of metaphysical and moral arguments in the development of Western pedagogical tradition of the 20th century.